Metagenomic insights into surface sediment microbial community and functional composition along a water-depth gradient in a subtropic deep lake - Zhang, Peixuan; Ren, Minglei; Xu, Yan; Wang, Jianjun (Frontiers in Microbiology, 2025)
Deep lakes play a critical role in global elemental cycling and serve as habitats for diverse microbial communities. However, studies on the effects of lake stratification on microbial composition and functional potential in surface sediments remain limited. Here, we investigated microbial community structure and functional composition using metagenomics of 38 surface sediments across a depth gradient of 0–90 m in Lugu Lake, China. Our results showed that Shannon diversity peaked at the thermocline for microbial communities, while a U-shaped pattern for functional genes. Microbial communities and functional genes in the surface sediments showed higher spatial heterogeneity at the shallow layer, whereas those at deeper layers tended toward more homogenized. Although water depth was the most important driver in explaining 29.9 and 26.5% of variance in microbial and functional gene composition, stochastic processes primarily governed the community assemblages, particularly dispersal limitation with the contribution of 43.7%. We further found the surface layer was enriched in genes mainly involved in aerobic metabolism and methanogenesis. In contrast, genes related to reduction reactions, including dissimilatory nitrate and sulfate reduction were more abundant in the thermocline and deep layer, reflecting lower redox potential in a deeper layer. Overall, our results provide evidence for microbial community stratification and functional partitioning in deep lakes.